The Influence of Good Corporate Governance on the Financial Stability of Indonesian Stock Exchange Manufacturing Companies with Technological Innovation as a Mediating Variable - Arvela Fadila Putri; Susi Sarumpaet (International Journal of Economics and Management Sciences, 2025)
Financial stability in manufacturing companies is an important issue, especially when facing national and global economic uncertainty. Good corporate governance is considered a framework that can drive technological innovation to enhance corporate excellence and achieve sustainable financial stability. This study aims to analyze the influence of the size of independent board of commissioners, managerial ownership, and institutional ownership on financial stability, with technological innovation as a mediating variable. The research data for this study were obtained from the annual financial reports of manufacturing companies listed on the Indonesia Stock Exchange for the period 2020 to 2023. Data analysis was performed using panel data regression and mediation testing using the Sobel test approach. The research findings indicate that the size of the independent board of commissioners has a positive effect on technological innovation, while managerial ownership has a negative effect and institutional ownership has no significant effect on technological innovation. However, the size of the independent board of commissioners, managerial ownership, institutional ownership, and technological innovation all have a significant effect on financial stability. The technology innovation variable also proved to mediate the influence of the size of the independent board of commissioners on financial stability. This finding emphasizes the importance of good corporate governance and technological innovation in maintaining the financial stability of manufacturing companies.